Hesychasm, Word-Weaving and Slavic Hagiography. The Literary School of Patriarch Euthymius - Hébert, Maurice L. (Sagners Slavistische Sammlung, 1992)
The aim of this study is to demonstrate that there is nothing new or peculiarly Hesychastic in the hagiographie style employed by Patriarch Euthymius, and that this style of "pletenie sloves" was borrowed by him and other medieval Slavic writers from an earlier and long existing Byzantine tradition that predated the Hesychast Revival. In effect, this study attempts to disprove one of the basic assumptions of present scholarship of the period of the Second South Slavic Influence.